A systematic review: Molecular docking simulation of small molecules as anticancer non-small cell lung carcinoma drug candidates - Syahrul Hidayat; Faisal Maulana Ibrahim; Cecep Suhandi; Muchtaridi Muchtaridi (Wolters Kluwer Medknow Publications, 2022)
Non-small cell lung carcinoma (NSCLC) is a type of lung cancer with the highest prevalence and mortality rate worldwide. Many cases of this type of cancer are overexpression on epidermal growth factor receptor (EGFR). The use of currently available EGFR inhibitors as one of the treatment options for NSCLC still shows various shortcomings, especially the high failure rate of therapy due to resistance. It is important to find NSCLC drug candidates with EGFR inhibitory activity. There are various published articles and it is prominent to draw evidence-based scientific conclusions as a basis of decision-making to select potential compounds for further research. Polymer matrix composites and ScienceDirect are used as a database for article screening. Research using molecular docking method targeted to EGFR with parameters of Gibbs energy and amino acid interactions between ligands and drug targets are included in inclusion criteria. Compounds that achieve docking parameters and have comparable activity to NSCLC guideline drugs are conscientiously ranked. There are only 11 compounds that achieved the docking parameters and had comparable EGFR inhibitory potential. Top-rated compounds include 1,3,5-trisubstituted pyrazoline (3c), 1,3,5-trisubstituted pyrazoline (6c), 1,3,5-trisubstituted pyrazoline (8d), N-(3,4-Dimethylphenyl)-2-[(4-oxo-3-(4-sulfamoylphenyl)-3,4-dihydrobenzo[g] quinazolin-2-yl) thio] acetamide. The top-rated compounds can be used and considered for further research processes.